Fast response and high stability Mn–Co–Ni–Al–O NTC microbeads thermistors. Issue 8 (16th April 2021) - Li, Haibing; Zhang, Huimin; Chang, Aimin; Ma, Xiuhua; Xie, Juntao; Yang, Linyu
Abstract: Herein, Al‐doped Mn1.95 Co0.21 Ni0.84 O4 (MCN)‐microbead structures were successfully prepared using in situ ink‐jet printing technology. The effects of the Al2 O3 doping on the electrical properties of the MCN ceramic microbeads were discussed. The R 25, B 25/50, and E a values of NTC ceramics thermistors were found to range from 14.14 × 10 3 ‒63.21 × 10 3  Ω, 3635‒3773 K, and 0.3133‒0.3252 eV, respectively. Notably, the ageing coefficient (Δ R / R ) of the (Mn–Co–Ni–Al–O) MCNA ceramics was found to be <1.1%, compared to a value exceeding 4.2% for the undoped MCN microbeads. The thermal time constant of the doped microbeads was small, with a value of 33 ms, compared to 8 s for the MCN ceramic chip. In particular, the grain boundaries were determined to play an important role in the overall electric behaviour of the ceramics described here.